The Impact of Intellectual Capital Efficiency on Financial Performance in the Indian Auto - Component Industry - Thiagarajan, Anthony; Baul, Utpal; Sekkizhar, J. (Indian Journal of Finance, 2018)
Purpose : The purpose of this paper was to study and discover the financial health of a company by measuring the relationship between the intellectual capital (IC) components with the traditional measures of organizational performance - financial, economic, and stock market. Design/Methodology/Approach : Using data from a sample of 42 listed companies from the Indian auto-component industry for the period from 2008 - 2013, this study applied the most attractive IC measurement model known for its practical and empirical validity (Zeghal & Maaloul, 2010). This measurement methodology is called the modified Value Added Intellectual Coefficient (M-VAIC) propounded by Nimtrakoon (2015). This is an optimized framework that improvises the popular and widely - used Value Added Intellectual Coefficient (VAICTM ) model of Pulic (2000, 2004, 2008) as addition of new variables to the VAICTM model improves its explanatory power. Findings : The Indian auto component manufacturing companies seemed to be performing effectively by utilizing their IC as seen by the empirical results during the period from 2008 - 2013 in spite of the economic recession of 2008 and its aftermath. Research Limitations/Implications : The results suggested that stakeholders still perceive the performance of firms in terms of tangible assets as the sole driver of organization success and less in terms of IC. This opens up avenues for further discovery/ findings to prove/disprove the same in other industries. Practical Implications : There is an imperative need for researchers, academics, business practitioners, and policy makers to get aware of IC and pitchfork it into the core of business. This study would benefit all stakeholders to achieve financial performance. Â Originality/Value : This is one of the pioneering attempts to measure IC and its relationship with the traditional measures of corporate performance in the Indian auto - component industry. This paper added to the existing literature by providing a new dimension of performance measurement.